I am just dancing: Am I just dancing ‐ A conversation between Amaara Raheem and Simon Ellis. Issue 2 (1st December 2021) - Raheem, Amaara; Ellis, Simon
In this conversation, dance-artist Amaara Raheem talks about her choreographic thinking and practice with CHOR co-editor Simon Ellis. They discuss Raheem's interest in dancing, ritual and research 'in-residence', and wonder about the kinds of bodies that dance. They consider how artists intentionally create the conditions for their work and practices to happen. The conversation is in part designed to introduce Raheem as a new co-editor to CHOR's readership.